2020
DOI: 10.3390/met10060765
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized and Non-Oxidized Multiwalled Carbon Nanotubes as Materials for Adsorption of Lanthanum(III) Aqueous Solutions

Abstract: The behavior of oxidized and non-oxidized multiwalled carbon nanotubes (MWCNTs) in the adsorption of lanthanum(III) from aqueous solutions is described. Metal uptake is studied as a function of several variables such as the stirring speed of the system, pH of the aqueous solution and metal and nanomaterial concentrations. The experimental results are fitted to various kinetic and isotherm models, the rate law being fitted to the film diffusion and particle diffusion models, when the non-oxidized and the oxidiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Linear fitting of functions c e /q e vs. c e , and lnq e vs. lnc e gave the parameters of the Langmuir and Freundlich models, respectively (Table 6). Additionally, the higher Fand R 2 values, as well as a lower p-value have shown that the Langmuir model is more suitable for the experimental data description than the Freundlich model, indicating that a homogeneous surface of adsorbent is covered with a single layer of adsorbed molecules [22].…”
mentioning
confidence: 99%
“…Linear fitting of functions c e /q e vs. c e , and lnq e vs. lnc e gave the parameters of the Langmuir and Freundlich models, respectively (Table 6). Additionally, the higher Fand R 2 values, as well as a lower p-value have shown that the Langmuir model is more suitable for the experimental data description than the Freundlich model, indicating that a homogeneous surface of adsorbent is covered with a single layer of adsorbed molecules [22].…”
mentioning
confidence: 99%
“…Solvent extraction is highly attractive for the recovery of valuable metals at high relative concentrations [1,3]; however, environmental impact (associated with organic losses) and economic constraints may limit its application in the case of dilute effluents. Ionexchange [4][5][6], chelating resins [7,8], impregnated resins [9], nanomaterials [10], carbon-based sorbents [11] or metal organic framework [12] offer complementary possibilities for the recovery of valuable metals from low-concentration solutions (less than 200 mg L − 1 ). Alternative materials proceeding from natural sources (biopolymers, biomass) have been used directly for the recovery of valuable metals [13,14 15,16] or after functionalization [17].…”
Section: Introductionmentioning
confidence: 99%
“…From several years ago, we have used the two particular adsorbents mentioned below in the removal of several metals from aqueous solutions [4,[34][35][36][37][38]. The reason is that both materials are easily accessible in the market and, based in our experience, represented good alternatives with respect to other adsorbents, at least in terms of availability and price.…”
Section: Introductionmentioning
confidence: 99%